Agriculture in an Urbanizing Society Volume One Proceedings of the Sixth AESOP Conference on Sustainable Food Planning - Roggema, Rob (Cambridge Scholars Publishing, 2016)
In two volumes, selected papers presented at the sixth AESOP conference on Sustainable Food Planning are brought together, representing the academic work of worldwide experts in the fields of food planning and urban agriculture. This volume, therefore, provides an overview of the latest, state-of-the-art research in the field, drawing from areas such as spatial planning, urban design, governance, social innovation, entrepreneurship, and local initiatives, among others, to represent the current knowledge base for creating sustainable urban food projects